Enzymatic utilization of oil and lignocellulosic biomass using halophilic marine bacteria Micrococcus luteus and Pseudoalteromonas peptidolytica - Johnson, Jervian; Choi, Kwon Young (3 Biotech, 2021)
In this study, hydrolytic and oxidative activities of enzymes isolated from halophilic microbes were characterized and applied for biomass utilization. First, lipase from Micrococcus luteus, and peroxidase and laccase from Pseudoalteromonas phenolica and Pseudoalteromonas peptidolytica were selected and their catalytic activities were determined, respectively. The M. luteus lipase encoding gene was synthesized after codon-optimization and could be successfully expressed in Escherichia coli with the assist of the Tif chaperone protein. The purified enzyme showed 119.13 ± 7.18 and 34.42 ± 5.91 U/mL of lipase and esterase activities, respectively. Moreover, the M. luteus lipase was applied for hydrolysis of the triglycerides mixture, which resulted in 182.9 ± 11.1 mg/L/h of glycerol productivity. Next, peroxidase and laccase activities of P. phenolica and P. peptidolytica were determined, and extracellular enzymes of P. peptidolytica was applied for lignocellulosic biomass degradation, which resulted in 91.9 μg glucose/mg lignocellulose of production yields. Finally, the hydrolytic and oxidative activities of the enzymes from halophilic microbes could be further utilized for biomass treatment and biochemical production.
Keywords: Esterase; Halophilic organism; High salt resistance; Lignocellulosic biomass; Peroxidase